A Correlation between Student’s Mastery of Past Tense and Their Achievement in Writing Narrative Text - Ahmad Zainuddin; Gusti Nurhafifah; Armeria Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
This research purposed to search and find out the correlations between students’ mastery of past tense and their achievement in writing narrative text. The method in this research used a purposive sampling technique with total sample 30 students. In this research, the data are obtained using two kinds of test namely Grammar and writing test. Meanwhile, the data were analyzed using Product Moment Pearson. The outlays of this research, the average score of past tense is 69,33and writing score is 77,33. Thus, the final result in this research when the formula correlation is applied, the score is 0,797 or substantial. It means that the r value is higher than r table; students’ master past tense influence to writing narrative text. It can be concluded that there is a positive correlation between students’ mastery of past tense and their achievement in writing narrative text